Reversal of Early Diabetic Nephropathy by Islet Transplantation under the Kidney Capsule in a Rat Model. (20th September 2016) - He, Yunqiang; Xu, Ziqiang; Zhou, Mingshi; Wu, Minmin; Chen, Xuehai; Wang, Silu; Qiu, Kaiyan; Cai, Yong; Fu, Hongxing; Chen, Bicheng; Zhou, Mengtao
Abstract : Objective . Diabetic nephropathy (DN) is a common microvascular complication of diabetes mellitus, and insulin therapy has many side effects in the treatment of DN. Islet transplantation has emerged as a promising therapy for diabetic patients. This study was established to investigate its advantageous effects in a rat model of early DN. Methods . Streptozotocin was administered to the rats to induce diabetes. Twelve weeks later, the diabetic rats were divided into 3 groups: the islet-transplanted group (IT group), the insulin-treated group (IN group), and the untreated group (DN group). Renal injury and kidney structure were assessed by urinalysis and transmission electron microscopy (TEM) detection. Immunohistochemical staining and western blotting were performed to assess renal fibrosis levels. Results . The early DN features were reversed and the glomerular filtration barrier and basement membrane structures were improved at 4 weeks after islet transplantation. The urine microalbumin-to-creatinine ratio (ACR), protein-to-creatinine ratio, and mean thickness of the glomerular basement membrane (GBM) were significantly decreased in the IT group. The expression of renal fibrotic factors was also significantly decreased. Conclusions . These data suggest that early DN can be reversed after islet transplantation, and they may facilitate the development of a clinical therapeutic strategy for human diabetes mellitus.